THE USE OF REALIA TO IMPROVE STUDENTS’ DESCRIPTIVE WRITING - Andini, Andini; Sofian, Sofian; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractStudents’ vocabulary mastery in writing descriptive text of class VIII A at SMP Jasa Mulia Sungai Baru were still weak. This research was conducted to improve students’ in writing descriptive text by using realia. This research used Classroom Action Research (CAR) and the participants of this research were twenty one students of class VIII A at SMP Jasa Mulia. The participants were taught to write descriptive text by using realia. Field notes, observation checklist and writing test were used to gather the data. The students’ score have improved significantly. The result on second cycle there was 28.6 % students could write descriptive text well. The result on third cycle was 86 % students got good score and could write descriptive text well. The process of students in the classroom and students’ score reflected that the realia can help students’ problem in writing a descriptive text. Otherwise, the realia need other help such as teacher’s explanation, example and guided questions.Key words: Descriptive Text, Realia, Writing.